Porous Colloidal Hydrogels Formed by Coordination‐Driven Self‐Assembly of Charged Metal‐Organic Polyhedra. Issue 9 (19th March 2021) - Wang, Zaoming; Craig, Gavin A.; Legrand, Alexandre; Haase, Frederik; Minami, Saori; Urayama, Kenji; Furukawa, Shuhei
Abstract: Introduction of porosity into supramolecular gels endows soft materials with functionalities for molecular encapsulation, release, separation and conversion. Metal‐organic polyhedra (MOPs), discrete coordination cages containing an internal cavity, have recently been employed as building blocks to construct polymeric gel networks with potential porosity. However, most of the materials can only be synthesized in organic solvents, and the examples of porous, MOP‐based hydrogels are scarce. Here, we demonstrate the fabrication of porous hydrogels based on [Rh2 (OH‐bdc)2 ]12, a rhodium‐based MOP containing hydroxyl groups on its periphery (OH‐bdc=5‐hydroxy‐1, 3‐benzenedicarboxylate). By simply deprotonating [Rh2 (OH‐bdc)2 ]12 with the base NaOH, the supramolecular polymerization between MOPs and organic linkers can be induced in the aqueous solution, leading to the kinetically controllable formation of hydrogels with hierarchical colloidal networks. When heating the deprotonated MOP, Nax [Rh24 (O‐bdc)x (OH‐bdc)24‐x ], to induce gelation, the MOP was found to partially decompose, affecting the mechanical property of the resulting gels. By applying a post‐synthetic deprotonation strategy, we show that the deprotonation degree of the MOP can be altered after the gel formation without serious decomposition of the MOPs. Gas sorption measurements confirmed the permanent porosity of the corresponding aerogels obtained from these MOP‐based hydrogels, showing potentials for applications in gas sorption and catalysis. Abstract : Two different routes were developed for the fabrication of porous hydrogels by coordination‐driven self‐assembly of OHRhMOP . Depending on whether the OHRhMOP was pre‐deprotonated before gelation or post‐synthetically deprotonated after the gel formation, hydrogel systems with different deprotonation degree and decomposition degree can be obtained, leading to the control of gel properties especially mechanical stiffness and porosity.